Information System For Monitoring Of Pregnant Mother In Riau Province Health Office - Mardeni Mardeni (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2020)
The data collection of pregnant women is the realization of the Birth Planning and Prevention of Complications (P4K) Program in the Riau Provincial Health Office of the Family and Nutrition Health Section. The data collection of pregnant women aims to find out information about pregnant women scattered in 12 regencies and cities in Riau Province including: the number of pregnant women, Tabulin, transportation, blood donors, assisting pregnant women and birth assistance plans. Currently reports and data recording of pregnant women are still done manually using Excel. To make it easier for officers to monitor the health of pregnant women in Riau Province, a Web based health monitoring system for pregnant women was built. This system integrates data on pregnant women in Riau Province starting from the Puskesmas level. This system can help officials in the Health Department monitor and record pregnant women, so that they can assist in planning a safe delivery and preparing for complications for pregnant women.